COVID-19 Preventative Measures: Bandanas as Cloth Face Coverings - Michelle D. Danyluk; Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman (EDIS)
This one-page full-color handout depicts two options for folding a plain bandana and describes the following: